Outcomes from the National High Secure Learning Disability Service: findings and challenges. Issue 3 (5th May 2015) - Morrissey, Catrin; Hobson, Ben; Faulkner, Emma; James, Tamsin
Abstract : Purpose: – The "outcomes revolution" in healthcare has yet to impact strongly on secure intellectual disability (ID) services in the UK. The purpose of this paper is to review the service-level outcome studies that exist for this population, and to explore some of the challenges of conducting such research. It further describes some illustrative routine outcome data from the National High Secure Learning Disability Service. Design/methodology/approach: – Routinely collected outcome measures (length of stay; violent incidents; Emotional Problem Scale (EPS) Behaviour Rating Scale and EPS Self-Report Inventory) were analysed for two overlapping cohorts of patients resident in the high-secure service between 2008 and 2013. Findings: – The median length of stay of those discharged during the study period ( n =27) was around 9.9 years (range one to 40 years). A significant proportion (25 per cent) of discharges resulted in an eventual return to high security. There did not appear to be a treatment effect over two to three years using staff-rated global clinical measures, but patient-rated clinical measures did reduce. Violent incidents also reduced significantly over a longer period of four years in treatment. Research limitations/implications: – There are identified challenges to research design and outcome measurement which need to be addressed in any future cross-service studies. Originality/value: – There are relatively few published outcome studies from forensic ID services. None of the studies have used clinical measures of changes or patient-rated outcome measures.